Caracterización de las prácticas de ganadería regenerativa implementadas en la parroquia Huamboya, Cantón Huamboya, provincia de Morona Santiago: Estudio de caso - Ramón Patiño, Alvaro Bladimir (2024)
This research, developed in the Huamboya parish, Huamboya Canton, Morona Santiago Province, Ecuador, explores the implementation of sustainable practices as a solution to the challenges of conventional livestock production. Regenerative livestock farming, which seeks to optimize soil health, biodiversity and water quality, is presented as a promising alternative to traditional methods. Using a mixed qualitative and quantitative approach, 17 regenerative livestock practices were identified, including the reforestation of pastures with endemic species, rotational grazing and the presence of perennial legumes. The study revealed a remarkable adoption of these practices, influenced by factors such as land structure, formal education of farmers, and training in regenerative livestock farming practices. The results indicate positive progress towards the adoption of sustainable practices, with a significant impact on the conservation of the Amazon ecosystem and improvement of livestock productivity. The research highlights the need for education and awareness strategies to increase the adoption of regenerative livestock farming, ensuring the sustainability and resilience of livestock production in the region.